Pengaruh Return In Asset, Debt To Equity Ratio dan Current Ratio Terhadap Harga Saham pada Industri Manufaktur Sub Sector Makanan dan Minuman Periode 2019-2022 - Hartono, Alfredo; Karnawati, Yosevin (Ikatan Da'i Indonesia, 2024)
This study's goal was to examine how the Production Industry's Return on Assets, Debt to Equity Ratio, along with Current Ratio affected share prices in the foods and beverages subsector from 2019 to 2022. Purposive sampling is used in this research to obtain financial along with annual reports from the Indonesia Stock Exchange's official website. The analysis approach used is multiple regression. This study obtained 72 data. The findings demonstrated that the current ratio, debt to equity ratio, as well as return on assets overall substantially increased stock prices. While the coefficient of determination (Adjusted R2) value is 23.8%, which means that the contribution of return on assets, debt to equity ratio along with current ratio in explaining the stock price is 23.8%.